Delivery Times and Delay in Delivery of Consignment under the Conditions of International Carriage - Jarmila Sosedová; Zuzana Otáhalová; Andrej Dávid; Andrea Galieriková (Communications - Scientific letters of the University of Zilina, 2021)
Delivery time means a certain period in which the carrier is obliged to transport the consignment from one place to another. The delay occurs when the carrier does not deliver the consignment to the consignee within this period. The authors analyse individual legislative documents regulating the transport - legal conditions of international transport. In addition, they present the reasons for the delay in delivery of the consignment and point to the carrier's liability for non-fulfilment of the obligation to transport the consignment within the delivery period. By comparing the results, authors state that there is a diversity of regulations in the field of international transport, especially in the context of the multimodality development. Such a diversity in regulations causes inconsistencies in the transport market and therefore there is a need to harmonize unimodal transport systems.